2020
DOI: 10.1029/2020gl089057
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Ice Exposing Scarps Within the Northern Midlatitude Craters on Mars

Abstract: We report new exposures of water ice along the scarps wall located within craters in the northern midlatitude region of Mars using high‐resolution imagery and spectral data of Mars Reconnaissance Orbiter. The exposed water‐ice deposits are shallower and exhibit 1.5 and 2 μm absorption. These scarps are located on the pole‐facing walls and equator‐facing wall origin floor deposits which formed over the latitude dependent mantle. Our observations advance in bracketing the younger ice deposits through the crater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(111 reference statements)
1
8
1
Order By: Relevance
“…Black dotted lines correspond to wavelengths of 1.5, 2.0, 3.03, and 3.62 µm. (Carrozzo et al, 2009;Vincendon et al, 2010;Harish et al, 2020) exhibit a 1.5 µm absorption of a few percent depth along with a stronger 2 µm absorption feature, while we do not detect these features. Very small water ice particles are needed to produce a 3 µm band without detectable feature at = 1.5 µm: an optical path length of only 4 µm within ice is supposed to be sufficient for OMEGA to detect ice at = 1.5 µm according to Vincendon et al (2010).…”
Section: Ratioed Reflectancecontrasting
confidence: 85%
See 1 more Smart Citation
“…Black dotted lines correspond to wavelengths of 1.5, 2.0, 3.03, and 3.62 µm. (Carrozzo et al, 2009;Vincendon et al, 2010;Harish et al, 2020) exhibit a 1.5 µm absorption of a few percent depth along with a stronger 2 µm absorption feature, while we do not detect these features. Very small water ice particles are needed to produce a 3 µm band without detectable feature at = 1.5 µm: an optical path length of only 4 µm within ice is supposed to be sufficient for OMEGA to detect ice at = 1.5 µm according to Vincendon et al (2010).…”
Section: Ratioed Reflectancecontrasting
confidence: 85%
“…When some subsurface water ice was exposed in a trench dug by the Phoenix robotic arm, observations showed that it quickly sublimated (Arvidson et al, 2009), so permafrost is unstable at the surface. However, local exposure of pergelisol outcrops have been reported in the northern mid-latitudes on pole-facing slopes (Dundas et al, 2018;Harish et al, 2020;Dundas et al, 2021). These are subpixel compared to OMEGA resolution, and we could expect such subsurface ice exposures to be more frequent in the northern high latitudes.…”
Section: Exposed Surface Water Icementioning
confidence: 92%
“…Some smaller and less well-defined exposures are included here, but more probably remain to be discovered. The two scarps reported by Harish et al (2020) were independently identified by our survey, supporting its effectiveness in identifying scarps at these scales.…”
Section: Ice-exposing Scarpssupporting
confidence: 59%
“…CRISM data confirm exposed ice at several scarps (Table S1) beyond those described in Dundas et al (2018). Detections at two of the scarps were independently confirmed by Harish et al (2020). Notably, one observation of the icy scarp at 57°N, 95.7°E (northern scarp site #4) shows a distinct water ice signature, DUNDAS ET AL.…”
Section: 1029/2020je006617mentioning
confidence: 52%
See 1 more Smart Citation